The Chemistry of Thermal Food Processing Procedures - Micali, Maria; Fiorino, Marco; Parisi, Salvatore (Chemistry of Foods,, 2016)
This Brief reviews thermal processes in the food industry - pasteurization, sterilization, UHT processes, and others. It evaluates the effects on a chemical level and possible failures from a safety viewpoint, and discusses in how far the effects can be predicted. In addition, historical preservation techniques - smoking, addition of natural additives, irradiation, etc. - are compared with current industrial systems, like fermentation, irradiation, addition of food-grade chemicals. The Brief critically discusses storage protocols - cooling, freezing, etc. - and packing systems (modified atmosphere technology, active and intelligent packaging). Can undesired chemical effects on the food products be predicted? This Brief elucidates on this important question. On that basis, new challenges, that currently arise in the food sector, can be approached.